2008
DOI: 10.1007/s11136-008-9429-z
|View full text |Cite
|
Sign up to set email alerts
|

Estimating health utilities in patients with asthma and COPD: evidence on the performance of EQ-5D and SF-6D

Abstract: Results suggest the EQ-5D and SF-6D do not yield consistent utility values in patients with asthma and COPD due to differences in underlying valuation techniques and the EQ-5D's limited response options relative to mild disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 31 publications
6
39
0
3
Order By: Relevance
“…Különböző betegségekben végzett hazai keresztmetszeti kérdőíves vizsgálatokban többször alkalmazásra került az EQ-5D kérdőív a betegek egészségi állapotának felmérésére, mint például a psoriasis [3,4,5,6], rheumatoid arthritis [7,8,9,10], jóindulatú prosztatamegnagyobbodás [11], epilepszia [12], perifériás artériás obliteratív érbetegség [13], sclerosis multiplex [14], hiperaktív hólyag szindróma [15], szkizofrénia [16], kró-nikus obstruktív tüdőbetegség (COPD) [17,18], demencia [19], Parkinson-kór [20,21,22], arthritis psoriatica [5,23], asztma [17,24] és 2-es típusú cukorbetegség [25] esetében.…”
Section: Rövidítésekunclassified
“…Különböző betegségekben végzett hazai keresztmetszeti kérdőíves vizsgálatokban többször alkalmazásra került az EQ-5D kérdőív a betegek egészségi állapotának felmérésére, mint például a psoriasis [3,4,5,6], rheumatoid arthritis [7,8,9,10], jóindulatú prosztatamegnagyobbodás [11], epilepszia [12], perifériás artériás obliteratív érbetegség [13], sclerosis multiplex [14], hiperaktív hólyag szindróma [15], szkizofrénia [16], kró-nikus obstruktív tüdőbetegség (COPD) [17,18], demencia [19], Parkinson-kór [20,21,22], arthritis psoriatica [5,23], asztma [17,24] és 2-es típusú cukorbetegség [25] esetében.…”
Section: Rövidítésekunclassified
“…Instruments that can differentiate between groups or severity levels with statistical Szende et al, [33] Hungary, Sweden significance or by pre-determined clinically important differences are more likely to reflect differences in HR-QOL when there are distinctions. Studies that include MAU measures have reported utilities based on COPD severity level diagnosed, mostly categorized based on the GOLD classification using FEV 1 .…”
Section: Stable Chronic Obstructive Pulmonary Disease (Copd) Severitymentioning
confidence: 99%
“…32,37,39 Few studies have been devoted to the comparison of the EQ-5D and the SF-6D in the general population, 45,58 along with the comparison of their performances for more than one disease. 35,59 The pattern of findings of most of these studies is that the EQ-5D tends to generate higher utility values than the SF-6D in groups with better states of health, whilst the opposite usually occurs in groups with worse health states. Furthermore, the conclusions of these studies have indicated a ceiling effect in the EQ-5D and a floor effect in the SF-6D, especially in patients with more serious illnesses.…”
mentioning
confidence: 99%